2014
DOI: 10.1155/2014/796510
|View full text |Cite
|
Sign up to set email alerts
|

Alendronate versus Raloxifene for Postmenopausal Women: A Meta-Analysis of Seven Head-to-Head Randomized Controlled Trials

Abstract: Purpose. The aim of this study was to directly compare the efficacy and the safety of the two agents for postmenopausal women. Methods/Principal Findings. Electronic databases were searched for relevant articles that met our predefined inclusion criteria. Seven randomized controlled trials (RCTs) involving 4054 women were identified and included. Although Aln was more effective than Rlx in increasing bone mineral density (BMD), no statistical differences were observed in reducing the risk of neither vertebral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 45 publications
(115 reference statements)
0
5
0
Order By: Relevance
“…No statistically significant results were found based on route of administration of bisphosphonates, nor between raloxifene and alendronate. Previous randomized trials and retrospective studies have found no difference between alendronate and raloxifene, and other reviews and analyses have concluded that minimal differences in efficacy exist between different medication options ( 4 , 14 - 16 ). The fact that our study did not find statistically significant differences supports the results from these studies.…”
Section: Discussionmentioning
confidence: 96%
“…No statistically significant results were found based on route of administration of bisphosphonates, nor between raloxifene and alendronate. Previous randomized trials and retrospective studies have found no difference between alendronate and raloxifene, and other reviews and analyses have concluded that minimal differences in efficacy exist between different medication options ( 4 , 14 - 16 ). The fact that our study did not find statistically significant differences supports the results from these studies.…”
Section: Discussionmentioning
confidence: 96%
“…While unmeasured confounding and differences in study populations and adherence preclude direct comparisons of associations with those from prior observational and randomized studies, these prior estimates can provide a rough guide about the direction and magnitude of the expected results. Thus, we expected the topperforming calipers to produce results close to the null in the raloxifene example, results slightly below the null in the simvastatin + ezetimibe example, and results substantially below the null in the COX-2 inhibitor example (18)(19)(20)(21).…”
Section: Discussionmentioning
confidence: 99%
“…Prevailing clinical wisdom favors alendronate as the first-line treatment option for osteoporosis patients against fracture [26][27][28][29][30] . However, head-to-head randomized studies of alendronate vs raloxifene have only shown increased bone mineral density with alendronate 31,32 , which do not necessarily relate to clinically observed fracture risk 6,9 .…”
Section: Discussionmentioning
confidence: 99%
“…The bisphosphonate alendronate and the selective estrogen receptor modulator (SERM) raloxifene are among the most popular antiresorptive agents for the prevention and treatment of postmenopausal osteoporosis 6,7 . Based on existing randomized studies that compare alendronate and raloxifene separately to placebo 8,9 , alendronate seems to have superior fracture prevention benefits.…”
mentioning
confidence: 99%